Othello on Trial: The Politics of Performance. Issue 2 (2nd July 2016) - Howe, Adrian
Abstract : This article tells the story of what happened when a feminist researcher tried to get her play, Othello on Trial, performed in London. A sanitised version of that story can be found elsewhere. This is the warts and all version written to highlight issues arising from the production that are of potential interest to feminist academics thinking about ways of gaining traction for their research outside the academy. For it is an essential part of the story that the politics of production and performance were to become inextricably entwined with the politics of the play, that is, with the whole question of the politics of voice – or 'voice potential' as Shakespeare's Iago puts it in Othello – that the Othello Theatre in Education project is designed to address.